African traditional religion in the modern world - Thomas, Douglas E. (Jefferson, N.C. : McFarland, 2005)
"This study analyzes concepts in African traditional religion by isolating key elements in the Yoruba, Dagara, and Ibo cultures. Principal elements isolated include sacrifice, salvation, revelation and divination, as well as African resilience in the face of invasions, colonization and various outside religious assaults. The study also considers the influence of Christianity and Islam"--Provided by publisher.
Includes bibliographical references (p. 193-198) and index.
Keywords: Christianity -- Influence; Islam -- Influence; Africa -- Religion